(untitled) (Economics and region, 2021)
The article analyzes the peculiarities of the implementation of companies’ innovation policy in terms of increasing competition. It is noted that the modern world economy is characterized by the need for constant innovation and flexibility of companies to survive in a turbulent environment. It is innovation that becomes the driving force of development and survival of companies in today’s market. The importance of the latest developments and innovations is not limited to the microeconomic level of specific businesses. Innovations are of great importance for the development of countries and the world community as a whole. The aim of the article is to analyze the innovation policy of modern corporations in conditions of international competition. A market economy, characterized by fierce competition, requires a special approach to innovation. Aiming to increase the efficiency of activities, innovations open wide prospects for the development of modern corporations. Successful innovation enables the company to form a positive image, increase competitiveness, use limited resources more efficiently, increase profits. The article emphasizes that the innovative type of development has a special impact on the company’s management, its goals, functions, methods, forming a special autonomous core – innovation management, which directs and regulates the whole set of innovation and investment processes in the economic system to ensure complex integration science, production and market. It is noted that it is important for the company not only to develop a new product, but also to make it competitive in the market. Competitiveness of a new product (or technology) means its ability to meet the demands and requirements of the market in a certain period of time and to be sold profitably if there are offers of other similar products (or technologies) on the market. The work highlights the motives for creating and selling innovations and the factors that determine them. The main motives for buying innovations are outlined. The current state of the world economy is characterized by clear changes in outdated views on methods and ways of doing business. Turbulence has become the basis of all human activities. Thus, in order to maintain a competitive position in the market, even the giants of the industry are forced to resort to constant quality renewal of their activities. The article highlights significant modern world trends in the introduction of innovations by companies. Two models of innovation policy are described - American and Japanese. In conclusion, it can be noted that scientific and technological progress, accelerating the development of information and communication technologies, transport and transportation, contributes to the growth of international contacts, connecting the hemispheres and continents of the world. In order to maintain a competitive position in the market in a turbulent economy, companies must take care of the constant renewal of their economic activities. Thus innovations are a product not only of technological developments, but also qualitative updating of management processes at the enterprise.